ANALISIS OMZET PENJUALAN PADA CV. KALDERA PANEN PERTIWI DITENGAH PANDEMI - Berto Pilipus Manihuruk; Eki Dudi Darmawan (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The number of competitors coupled with the COVID-19 pandemic is a factor that affects sales turnover at the company, because sales turnover is important to realize the company's goals. CV. Caldera Panen Pertiwi Bandung branch is a meat distributor company and the only branch in the city of Bandung. The purpose of this study was to determine the analysis of market segmentation on sales turnover in the midst of the covid-19 pandemic, to determine the impact that occurred and the efforts made to increase sales turnover. This research includes inductive qualitative research using descriptive qualitative analysis techniques, where this study tries to explain the solution to existing problems based on existing company data. The results of the study that caused the decline in sales turnover during this pandemic were limited availability or supply of stock from abroad, unstable raw material prices or goods prices, then less demand for goods, then central and regional government policies which of course had an impact on companies or distributors. meat because many places of business are temporarily closed. Keywords: Turnover, Sales, Covid-19 Pandemic